Digital Transformation in Improving Legal Services by Notaries Who Apply the Cyber Notary Concept - Rizka Syafriana; Ida Hanifah; Onny Medaline (FASYA Press, 2025)
The era of Digital Disruption is marked by the shift in people's activities from conventional systems to information technology-based systems that prioritize efficiency and flexibility. The development of the internet and digital economy also affects the field of notary, so notaries are required to be able to adapt through the use of technology in carrying out their duties as makers of authentic deeds. The regulation of electronic transactions in Law Number 11 of 2008 concerning Information and Electronic Transactions and the authority of notaries in the Law on Notary Positions are the normative basis in studying the application of the concept of cyber notary. The problems of this research include the application of cyber notary in improving legal services, factors that hinder its implementation, and regulatory models relevant to digital transformation. This research aims to make a theoretical contribution to the development of notary literature related to cyber notaries as well as practical contributions for notaries and the public in understanding digital transformation in the legal field. The method used is normative-empirical research with a legislative approach and qualitative analysis of primary and secondary legal materials. This research is explanatory and prescriptive analytical. The results of the study show that the implementation of cyber notary still faces juridical obstacles, especially related to the limits of authority, the validity of the deed, and the strength of legal proof. The absence of special regulations regarding cyber notaries in the Indonesian legal system is the main obstacle in its implementation. In conclusion, digital transformation in notary is an inevitable need in the era of globalization. However, in order for the implementation of cyber notary to run effectively and provide legal certainty, progressive, comprehensive, and adaptive regulatory reforms are needed to bridge the gap between technological developments and the national legal system.